Development of a Multi-Session Curriculum Addressing Domestic Minor Sex Trafficking for High-Risk Male Youth. Issue 6 (18th August 2021) - Fitzgerald, Meagan; Owens, Timothy; Moore, Jessica; Goldberg, Amy; Lowenhaupt, Elizabeth; Barron, Christine
ABSTRACT: Males, in particular adolescents and young adults, have been increasingly recognized as involved in domestic minor sex trafficking (DMST). However, there are very sparse resources and organizations that provide prevention, identification, and interventions for boys and young men who are involved in or at-risk for DMST involvement. The objective was to develop and assess an educational curriculum to prevent adolescent male involvement in DMST through a three-pronged educational approach: as victims of sexual exploitation; receiving financial benefit as exploiters; as buyers of sex. Through quality improvement cycles, changes were made to enhance the curriculum by utilizing the outcome measures of participant questionnaires and feedback from a steering committee of clinical experts. Male youth at the state's juvenile detention center were asked to participate in pilot groups, as they were identified as a high-risk population of adolescents to become involved. The curriculum was modified by adding sessions, including additional community guest speakers, and providing a more holistic educational experience that involves trafficking prevention from both a victimization and perpetration standpoint. Our goal is to expand this educational opportunity to be utilized in multiple settings (e.g., schools, hospitals) across the country.